New age crop production technology to boost farmers’ income - Singh, Brahma (Indian Horticulture, 2019)
To promote promising protected cultivation technology, low-cost protected cultivation technologies may be promoted for large-scale production of horticulture crops in pre-urban areas and vegetable/horticulture clusters throughout the country keeping in view local conditions, climate, soil and natural resource. Extensive training of youths to grow, process and market horticultural produce using protected cultivation technologies will create employment, income and more nutritive food supply for human health. Being a different, distinct, and new area involving vast multidisciplinary aspects of agriculture, establishing schools of protected horticulture/agriculture would be of great help to generate appropriate human resource and technologies including soilless cultivation, hydroponics, aeroponics, vertical vegetable production, mechanization and maintenance of polyhouses/structures, pollination devices, robotics, vegetable/fruit grafting, specialized disease-free seed production, use of pollinators, container farming, organic protected cultivation, good horticulture production practices, water harvesting and postharvest handling of produce and importance of providing disease free healthy plant nursery including grafts in plug trays containing soilless medium. Thus, Indian farmers may like to adopt protected horticulture to double their income.